Targeting the NRF2 pathway for disease modification in neurodegenerative diseases: mechanisms and therapeutic implications - Mayer, Clara; Riera-Ponsati, Lluís; Kauppinen, Sakari; Klitgaard, Henrik; Erler, Janine T.; Hansen, Stine N. (Frontiers in Pharmacology, 2024)
Neurodegenerative diseases constitute a global health issue and a major economic burden. They significantly impair both cognitive and motor functions, and their prevalence is expected to rise due to ageing societies and continuous population growth. Conventional therapies provide symptomatic relief, nevertheless, disease-modifying treatments that reduce or halt neuron death and malfunction are still largely unavailable. Amongst the common hallmarks of neurodegenerative diseases are protein aggregation, oxidative stress, neuroinflammation and mitochondrial dysfunction. Transcription factor nuclear factor-erythroid 2-related factor 2 (NRF2) constitutes a central regulator of cellular defense mechanisms, including the regulation of antioxidant, anti-inflammatory and mitochondrial pathways, making it a highly attractive therapeutic target for disease modification in neurodegenerative disorders.Here, we describe the role of NRF2 in the common hallmarks of neurodegeneration, review the current pharmacological interventions and their challenges in activating the NRF2 pathway, and present alternative therapeutic approaches for disease modification.